1998
DOI: 10.1111/j.1096-3642.1998.tb01298.x
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic mechanical factors in the evolution of long bone epiphyses

Abstract: In developing vertebrate long bones in which endochondral ossification occurs, it is preceded or accompanied by perichondral ossification. The speed and extent ofperichondral apposition relative to endochondral ossification varies in different taxa. Perichondral ossification dominates early long bone development in extinct basal tetrapods and dinosaurs, extant bony fish, amphibians, and birds. In mammals and lizards, perichondral and endochondral ossification proceed more synchronously. One of the most importa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
67
0

Year Published

1999
1999
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(70 citation statements)
references
References 19 publications
3
67
0
Order By: Relevance
“…The effects of prenatal muscle kinesis in Bathyergus, as well as in many other subterranean species are almost completely unknown, and it may have an important impact on the normal development of epiphyses and joints such as the biepicondylar breadth, even when these regions are still chondroepiphyses. 93,94 Similarly, epicondyles are regions directly associated with sites for muscle and tendon attachment, thus receiving direct biomechanical stimulation as compared to regions without it (eg, diaphysis). Differences in load bearing stresses experienced at early perinatal stages also may contribute to the development of such features.…”
Section: Timing and Causes Of Ontogenetic Shifts In Bone Morphologymentioning
confidence: 99%
“…The effects of prenatal muscle kinesis in Bathyergus, as well as in many other subterranean species are almost completely unknown, and it may have an important impact on the normal development of epiphyses and joints such as the biepicondylar breadth, even when these regions are still chondroepiphyses. 93,94 Similarly, epicondyles are regions directly associated with sites for muscle and tendon attachment, thus receiving direct biomechanical stimulation as compared to regions without it (eg, diaphysis). Differences in load bearing stresses experienced at early perinatal stages also may contribute to the development of such features.…”
Section: Timing and Causes Of Ontogenetic Shifts In Bone Morphologymentioning
confidence: 99%
“…Due to this compression and the movement of the joints, 'pressure epiphyses' are under hydrostatic and shear stresses (Serrano et al, 2011). Arkin & Katz (1956), Carter & Wong (1988), Carter et al (1991Carter et al ( , 1998 found that these stresses decrease the rate of epiphyseal cartilage growth. 'Traction epiphyses' provide attachment for tendons and muscles and are subject to lateral stresses and tension (Parsons, 1904;Serrano et al, 2011).…”
Section: Growth Plate Closure Sequences In a Biomechanical Contextmentioning
confidence: 99%
“…The secondary ossification centres are usually tied to the evolution of determinate growth. Calcified and bony epiphyses evolved several times independently in many vertebrate lineages: Teleostei, Anura, Lepidosauria, Theria and possibly Aves (Haines, 1942;Carter et al, 1998). Although bony epiphyses have been reported in some kannemeyeriid dicynodonts, a group of nonmammaliaform synapsids (Walter, 1985), the lack of secondary ossification centres was hypothesized to be the plesiomorphic condition in cynodonts and mammaliaforms (Luo et al, 2007).…”
Section: Complete Growth Plate Closure and Lapsed Unionmentioning
confidence: 99%
“…There is reason to expect a patella in Sphenodon. Like the patella, secondary epiphyseal ossification centres have also evolved on repeated occasions, and generally appear to cooccur with sesamoids in many groups (Sarin et al 1999), suggesting that these two features are linked by some yet obscure developmental mechanism (Carter et al 1998). Non-avian dinosaurs, crocodiles, turtles and salamanders lack ossified epiphyses and sesamoids (though they may have cartilaginous sesamoid structures, e.g.…”
Section: Introductionmentioning
confidence: 99%